Disclosure of Sexual Violence Among Girls and Young Women Aged 13 to 24 Years: Results From the Violence Against Children Surveys in Nigeria and Malawi - Nguyen, Kimberly H. (Journal of interpersonal violence, 2021)
Understanding factors that are associated with disclosure of sexual violence (SV) is important for the delivery of health services as well as developing strategies for prevention and response. The Violence Against Children Surveys were conducted in Malawi and Nigeria. We examined the prevalence of SV, help-seeking behaviors, and factors associated with disclosure among girls and young women aged 13 to 24. The self-reported prevalence of SV was similar in Nigeria (26%) and Malawi (27%). Among females who experienced SV, approximately one third (37%) in Nigeria and one half (55%) in Malawi ever disclosed their experience of SV. Females in Nigeria were significantly more likely to disclose to their parents (31.8%) than females in Malawi (9.5%). The most common reason for nondisclosure in Nigeria was not feeling a need or desire to tell anyone (34.9%) and in Malawi was embarrassment (29.3%). Very close relationships with one or both parents were significantly associated with disclosure among Nigerian females (odds ratio [OR] = 5.5, 95% confidence interval [CI] = [2.1, 14.6]) but were inversely associated with disclosure among Malawian females (OR = 0.05, 95% CI = [0.01, 0.33]). Reasons for nondisclosure of SV and factors associated with disclosure among females differ in the African nations studied. The stigma associated with shame of SV may prevent females from disclosing and thus receiving necessary support and health, social, and other services. This study demonstrates a need to reduce barriers for disclosure to improve the delivery of health, social, and other response services across African nations, as well as to develop culturally appropriate strategies for its response.